2022
DOI: 10.37332/2309-1533.2022.2-3.14
|View full text |Cite
|
Sign up to set email alerts
|

Development of Critical Technologies in the Field of Energy Security of Ukraine

Abstract: Purpose. A study of approaches to understanding the essence of the concept of “critical technologies”, an overview of the development of critical technologies in the field of energy security of Ukraine and an outline of the features of their use in modern conditions and for the future. Methodology of research. The methodological basis of the research is the dialectical method of scientific knowledge. General scientific and special methods were used in the research process, in particular: analysis and synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
(1 reference statement)
0
2
0
1
Order By: Relevance
“…V.Ya. Brych et al (2022) analysed the development of technologies that are critical to ensuring Ukraine's energy security and increasing the stability and efficiency of the energy system. The study findings identified key areas of technology development that should be prioritised for implementation to ensure the reliability and optimisation of Ukraine's energy sector.…”
Section: Introductionmentioning
confidence: 99%
“…V.Ya. Brych et al (2022) analysed the development of technologies that are critical to ensuring Ukraine's energy security and increasing the stability and efficiency of the energy system. The study findings identified key areas of technology development that should be prioritised for implementation to ensure the reliability and optimisation of Ukraine's energy sector.…”
Section: Introductionmentioning
confidence: 99%
“…V.Ya. Brych et al (2022) analysed the development of technologies that are critical to ensuring Ukraine's energy security and increasing the stability and efficiency of the energy system. The study findings identified key areas of technology development that should be prioritised for implementation to ensure the reliability and optimisation of Ukraine's energy sector.…”
Section: Introductionmentioning
confidence: 99%
“…1. Освоєння нових технологій удосконалення енергетичних мереж та обладнання з урахуванням намірів їх гармонізації з енергетичною системою країн ЄС; Джерело: [8] Пріоритетними напрямами розвитку критичних технологій у міжнародній енергетичній сфері є такі:…”
unclassified